Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/978-3-030-14347-3_14
|View full text |Cite
|
Sign up to set email alerts
|

User Modeling on Twitter with Exploiting Explicit Relationships for Personalized Recommendations

Abstract: The use of social networks sites has led to a challenging overload of information that helped new social networking sites such as Twitter to become popular. It is believed that Twitter provides a rich environment for shared information that can help with recommender systems research. In this paper, we study Twitter user modeling by utilizing explicit relationships among users. This work aims to build personal profiles through a alternative methods using information gained from Twitter to provide more accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 17 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…Also, the recent activities of most users do not have sufficient data or URL data to enrich their profiles from them. To address the problem of data shortage, the authors in [4] showed that direct explicit links between users should be used for the purpose of enriching the user profile. This finding will help expand the recent activities that are relevant.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, the recent activities of most users do not have sufficient data or URL data to enrich their profiles from them. To address the problem of data shortage, the authors in [4] showed that direct explicit links between users should be used for the purpose of enriching the user profile. This finding will help expand the recent activities that are relevant.…”
Section: Related Workmentioning
confidence: 99%
“…They further stated that there is no agreement regarding who or what is an influential user. Subsequently, the authors in [4] argued that there is a need for creating a method which will be able to generate or produce an influence score based on the perspective of the normal user in relation to his or her interaction and behaviour. Their proposed influence score was higher when it identified influential friends of the user and then utilized those friends as a valuable source for building the user profile.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations